Security Challenges and Countermeasures in Next-Generation Wireless Networks - Manjunath, Honganur Raju; Yadav, Aditya; Sarpal, Sumeet Singh; Mounika, Nagireddy; Patil, Shashikant; Nandhitha, N.M.; Behera, Santosh Ku. (International Journal of Engineering, Science and Information Technology, 2025)
The prospects of new-age wireless networks, such as 5G and 6G technologies, include unrivalled speed, connectivity, and integration of multifarious devices. However, their sophisticated architecture— which encompasses network slicing, edge computing, massive IoT, and software-defined networking—creates even greater challenges in network security. These vulnerabilities could be exploited to launch advanced attacks such as Distributed Denial of Service (DDoS) attacks, eavesdropping, spoofing, or data manipulation. This study aims to explore the evolving threat landscape for next-generation wireless networks while reviewing both existing and emerging strategic solutions. Some of the counter-surveillance technologies incorporated include AI-based Intrusion Detection Systems, Trust Frameworks on Blockchain, strong cryptography, and credential-less authentication. Addressing the challenge of dynamic threat capabilities paired with innovative defences allows this research to propose concepts for the next resilient and secure wireless communication systems.